Therapeutic Management of Haemotoxic Snake Envenomation in Dogs – A Field Study - Hema Sayee, Rajamanickam; Thirumalaisamy, Govindasamy; Sivaraman, Subramanian; Mekala, Palanisamy (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Snake envenomation is a life threatening, emergency and  challenging case to be handled by veterinarians especially  in the rural parts of India. Out of 3500 different species of  snakes around the world, about 600 species were found to  be poisonous (Sandhu and Brar, 2008). In India, about 216  species of snakes are present, out of which 60 species are  reported to be poisonous (Gupta and Peshin, 2014). The  snake envenomation in livestock and companion animals  occurs commonly in summer months. It is more prevalent  in rural areas of India which are filled with bushes and trees  (Garg, 2002). Most snake bites occur usually on head and  extremities in small animals and on legs in large animals  (Sandhu and Brar, 2008). The clinical signs caused by the snake  envenomation depend upon the type of toxins present in the  venom. The neurotoxic venom causes paralysis of respiratory  centre /respiratory muscles, whereas haemotoxic venom  causes coagulopathies/bleeding disorders, haemolysis and  cardiotoxicity (Sandhu and Brar, 2008). The current paper  describes the haemotoxic snake envenomation in three dogs  and its therapeutic management.
Keywords: veterinarians; poisonous; prevalent; extremities; dogs